2019
DOI: 10.1111/sms.13463
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related physical and technical match performance changes in elite soccer players

Abstract: The age of peak performance is likely to vary between sports and competitions, affected by the specific skills and attributes needed to succeed in the particular competition. However, no studies using modern tracking techniques have examined the effects of age on competitive match play performance. Thus, the purpose of this study was to evaluate the effects of age on match physical and technical performance using a large‐scale analysis of match performance in professional soccer players. A total of 14 546 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 28 publications
13
20
2
Order By: Relevance
“…The findings reported above, which are based on measurements of isolated physiological capacities such as power generation and endurance, seem to correspond well with the findings of Sal de Rellán-Guerra et al (2019) , which are based on real soccer match performance. These authors reported that professional soccer players above 30 years of age ran significantly shorter distances and completed fewer fast runs and sprints during matches compared with players below 30 years of age.…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…The findings reported above, which are based on measurements of isolated physiological capacities such as power generation and endurance, seem to correspond well with the findings of Sal de Rellán-Guerra et al (2019) , which are based on real soccer match performance. These authors reported that professional soccer players above 30 years of age ran significantly shorter distances and completed fewer fast runs and sprints during matches compared with players below 30 years of age.…”
Section: Introductionsupporting
confidence: 84%
“…Midfielders generally have the highest maximal oxygen uptake among players in all positions ( Sporis et al, 2009 ; Tønnessen et al, 2013 ), and from our data, we identified an average age of peak performance for the total sample of midfielders to be 26.46 (27.53 for retired last nomination). Our estimated ages at peak performance relative to age variations in endurance capacity seem to reflect the findings on sprint performance, and they indicate that a decrease in endurance can be compensated for by improved performance regarding technical and tactical skills ( Sal de Rellán-Guerra et al, 2019 ). The midfielder Lothar Matthäus was nominated for Ballon d’Or in 1999 at the age of 37.8 years, being to date the oldest nominated midfielder.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations